Retained lens fragment presenting 32 years after cataract extraction - Thomas Tien; Marcos A. Crespo; Tatyana Milman; Zeba A. Syed (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To report a patient with retained lens material presenting over three decades after initial cataract extraction with fluctuating corneal edema and intraocular inflammation. Observations: A 66-year-old man presented with a first episode of decreased vision and photophobia 32 years after cataract extraction without intraocular lens implantation in the right eye. Slit lamp examination revealed a tan-colored oblong mass in the inferior angle, in addition to corneal edema and an anterior chamber reaction. The patient was aphakic with traumatic mydriasis, and accordingly it was noted that the mass shifted location between anterior and posterior chambers over subsequent evaluations. The anterior chamber inflammation resolved in the latter position. The patient was requested to remain prone prior to clinical evaluation, and an in-office anterior chamber aspiration was performed. Histopathologic evaluation confirmed the presence of lens material and a phacolytic response. Conclusions And importance: Although unusual, retained lens material may manifest with ocular morbidity decades after cataract extraction. In patients with corneal edema and intraocular inflammation, retained lens material should be considered as a possible underlying cause even in patients with a remote history of cataract extraction. This case represents one of the longest reported time periods from cataract extraction to clinical presentation of retained lens material.